2022
DOI: 10.3390/app122010400
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economics and the Identification of Environmental Barriers to the Development of Concentrated Solar Thermal Power Plants in India

Abstract: India is endowed with a lot of solar radiation as a result of its location. The Indian government therefore intends to maximize the usage of its solar energy resources through the development of solar power plants across the country. The concentrated solar power plant (CSP) is one of the technologies that rely on solar energy for its electricity generation. The type of condenser model in the CSP technology has the potential to affect its techno-economic viability. In this paper, a 100 MW solar tower power plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…where I l,h is the vector in the complex domain that contains the current flowing through the distribution lines of the system; Y p is the primitive admission matrix containing the inverse of the impedance of each line on its diagonal; and A is the incidence matrix. Likewise, to obtain the value of E cost and E CO 2 , it is necessary to calculate the power generated at the terminals of the conventional generator, as shown in (38).…”
Section: Slave Stage: Successive Approximations Power Flow Methodsmentioning
confidence: 99%
“…where I l,h is the vector in the complex domain that contains the current flowing through the distribution lines of the system; Y p is the primitive admission matrix containing the inverse of the impedance of each line on its diagonal; and A is the incidence matrix. Likewise, to obtain the value of E cost and E CO 2 , it is necessary to calculate the power generated at the terminals of the conventional generator, as shown in (38).…”
Section: Slave Stage: Successive Approximations Power Flow Methodsmentioning
confidence: 99%
“…The solar parabolic trough system does not directly release carbon dioxide (CO 2 ) during its operation because it does not use fossil fuels to generate heat. Using Equation (27) [19,81], it is possible to determine how much CO 2 is released during the process of making energy equivalent to that generated by the SPT system:…”
Section: Environmental Impact Evaluationmentioning
confidence: 99%
“…This method of concentrated solar collection has the advantage of high efficiency and can be used either for thermal energy collection, for generating electricity [16], or for both; therefore, it is an important way to exploit solar energy directly [17]. Furthermore, several studies have shown that solar concentrating plants have great prospects in terms of a low environmental impact and favorable technoeconomic factors [18][19][20][21]. For example, thanks to the use of solar concentrator power plants, India has avoided around 170,000 metric tons of CO 2 e per year [19], and Pakistan has avoided over 225,000 metric tons of CO 2 e per year [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, an estimation of CO 2 emission, which can be avoided due to electricity generation from the proposed HPGP, was calculated. This calculation was conducted using Equation ( 14) [58].…”
Section: Environmental Impact Assessmentmentioning
confidence: 99%